2014
DOI: 10.1039/c4ra00892h
|View full text |Cite
|
Sign up to set email alerts
|

One-pot production of hydrocarbon oil from poly(3-hydroxybutyrate)

Abstract: Decarboxylation of poly(3-hydroxybutyrate) (PHB) in a H3PO4 solution generates a renewable hydrocarbon oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Such low-quality mcl-PHA is accessible from the conversion of carbon-rich waste water samples by mixed bacterial cultures and this displays insufficient quality to be used as plasticof rubber-like material [67,68]. Similar attempts were recently reported by Kang and Yu [69], who chemically converted PHB to produce hydrocarbon oil in one-pot reactions at a mild temperature (around 220°C) using phosphoric acid as recyclable catalyst. This might be a future possibility to use spent items made of scl-PHA as an alternative to their anaerobic digestion to biogas or to composting.…”
Section: Follow-up Products Of Spent Phamentioning
confidence: 52%
“…Such low-quality mcl-PHA is accessible from the conversion of carbon-rich waste water samples by mixed bacterial cultures and this displays insufficient quality to be used as plasticof rubber-like material [67,68]. Similar attempts were recently reported by Kang and Yu [69], who chemically converted PHB to produce hydrocarbon oil in one-pot reactions at a mild temperature (around 220°C) using phosphoric acid as recyclable catalyst. This might be a future possibility to use spent items made of scl-PHA as an alternative to their anaerobic digestion to biogas or to composting.…”
Section: Follow-up Products Of Spent Phamentioning
confidence: 52%
“…In the reaction catalyzed with H 3 PO 4 , PHB was completely converted and deoxygenated to a great extent with formation of CO 2 and propylene (C 3 H 6 ), and more interestingly with formation of substantial amount of aromatic compounds. 5 We found that crotonic acid (CA, trans-2 butenoic acid, C 4 H 6 O 2 ), was a key monomeric intermediate in the early stage of PHB conversion. Under typical reaction conditions (100% H 3 PO 4 solution, 220 C and 3 hours), CA was completely converted and 90.9% of the original carbon was recovered from the gas and liquid products.…”
Section: Introductionmentioning
confidence: 93%
“…It has been reported that PHB reforming in phosphoric acid solutions (80-100%) occurs in a temperature range between 200 and 240°C [20,21], but it is not clear what is the lowest temperature or temperature range in which the reaction can occur on SPA catalyst. DSC analysis of a crude PHB and SPA420 mixture (mass ratio 1:1) revealed the interesting information as shown in Fig.…”
Section: Phb Reaction Temperaturementioning
confidence: 99%
“…According to our previous work using liquid phosphoric acid as the catalyst [20,21], a high concentration of acid is needed for the catalytic reforming of PHB. In this work, a broad range of the catalyst to PHB ratio was investigated.…”
Section: Influences Of Catalyst Calcination Temperature and Dosagementioning
confidence: 99%
See 1 more Smart Citation